Penurunan Minat Akibat Media Sosial terhadap Penggunaan Bahasa Indonesia yang Benar Oleh Generasi Muda - Afrizal Dwi Fajarizko; Moh. Emil Syamsudin; Denny Okta Radianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Language can be used as a condition for humans to think, which is the initial source for humans to obtain the process of understanding and knowledge. With the influence of social media, it has quite a big impact on people's lives. There are many new languages created by the millennial generation and generation Z in social media and survival. Considering that social media users have a very high number, this has resulted in a lot of language changes. The aim of writing this research is to provide readers with deeper knowledge of the influence of social media on the use of Indonesian in national and state life. This is proof that there has been a change in the Indonesian language due to social media. Various new languages have emerged and the standard Indonesian language has been contaminated, which should be upheld as the unified language and national language of the Republic of Indonesia.